Learning tactics inventory. - Dalton, Maxine A. (Center for Creative Leadership, 2016)
The Learning Tactics Inventory Facilitator's Guide will assist facilitators, trainers, and presenters with the resources to offer the optimal learning experience for those taking the self-scoring Learning Tactics Inventory. The guide offers: • An explanation of the underlying learning model; • Suggestions for presenting the model to others; • A description of inventory applications and uses; • A sample workshop design and administrative suggestions; • The underlying inventory's theory and research; • Suggested resources; and • Access to the Powerpoint slides.